Low strain rate testing of tensile properties of steel. (2020) - Baciu, Florin; Rusu-Casandra, Aurelia; Pastramă, Ştefan-Dan
Abstract: Tensile testing is one of the most important types of engineering tests used for all metallic materials that provides material characteristics. In this paper, experiments were performed on grade PC52 (0.22% C) steel specimens using an INSTRON 8801 universal testing machine to determine yield strength, tensile strength, strain at break and Young's modulus. Strain rates applied during tests were in the range characteristic for static tensile tests as recommended in standards ASTM Standard E8/E8M-16a and ISO 6892-1:2016, being typical for testing steel used for engineering components in applications such as storage tanks and pressure vessels. The influence of the strain rate on the values of the material properties was analyzed and the result was in agreement with reference literature. Coefficients of variation were calculated for the measured values of steel properties for different strain rates and compared to values prescribed in standards, leading thus to the recommendation of a specific value of strain rate for the tensile test of steel PC52.